Genetic structure of experimental populations and reproductive fitness in a heterocarpic plant Atriplex tatarica (Chenopodiaceae) - Mandák, Bohumil; Bímová, Katerina; Placková, Ivana (American journal of botany, 2006)
Atriplex tatarica is a heterocarpic species of disturbed habitats. Seeds of Atriplex tatarica do not germinate immediately after shedding, but may remain in a dormant but viable state indefinitely. We investigated whether there were genetic and fitness differences between plants derived from seeds of the different fruit types germinated in different temperatures and salinities. Seeds that germinated in optimal and suboptimal conditions differed significantly in their genetic composition due, in part, to their source population. Seeds that germinated in the suboptimal conditions produced more homozygous plants. Plants that were primarily heterozygous were generated from nondormant fruit types as well as from fruits that germinated in the optimal conditions. Moreover, there was a positive correlation between the degree of heterozygosity and plant fitness measured as the mass of the stem and reproductive structures. In conclusion, the genetic variation of natural populations may be at least partly due to the ability of particular seed genotypes to germinate in the specific environmental conditions of a particular locality. In some circumstances, the process of differential germination may select not only for genetic variability but also for higher fitness if heterozygosity-fitness correlations are present.